Scientific Reflection of Public Service Advertisement Concept in International Scope and Historical Aspects - Al Khudiry, Yaser Hamza Salman (Current Issues of Mass Communication, 2016)
In this research, for the first time in Ukraine, a large volume of foreign scientific sources on public service advertising (PSA) was analyzed that allowed to make an assessment of the differences in theoretical approaches to the determination of the PSA and of the main research vectors of exploring this social and communication phenomenon; an attempt to expand its theoretical and methodological fundamentals was taken. The study is based on qualitative analysis of 122 scientific sources. The data was systematized and generalized. Descriptive, comparative and empirical-analytical methods were used to make an objective assessment of the subject. System method was applied to link each item to its role and place in the system. It is shown in the research that scientific approaches to the concept of PSA are ambiguous; they vary depending on historical, cultural, political and other factors. More than half a century American as well as European scientists have been attempting to explore the PSA as a separate subject; currently, the most actual trends in public service advertising development relate to its applicable aspects, its social communication techniques and efficiency. Constantly expanding geography of the research contemplates a tendency towards deeper understanding of the subject, thanks to the outcomes of implemented information campaigns. Special attention in the PSA research is dedicated to the psychological factors of influencing audience, the latest communication channels, and specifics of the content. Considering the international experience and historical factors, the conceptual apparatus of public service advertising was specified in this research, and the ways for improving further scientific studies of the PSA in Ukraine are proposed.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTc3MjEvMjMxMi01MTYwLjIwMTYuMjAuNzEtODE